FAKTOR PERILAKU DAN FAKTOR LINGKUNGAN YANG BERHUBUNGAN DENGAN KEJADIAN MALARIA DI WILAYAH KERJA PUSKESMAS GEBANG KABUPATEN PURWOREJO - Laela Isnaeni; Lintang Dian Saraswati; M. Arie Wuryanto; Ari Udiyono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Malaria is an infectious disease and still become a public health problem in Indonesia. Malaria transmission is influenced by several factors such as the environment, agent, and host. Purworejo is one of sub-districts in Central Java that has the highest malaria rate. One endemic sub-district in Purworejo is Gebang with MOPi in the early quarter of 2018 at 1.3 ‰. The purpose of this study was to analyze the relationship between environmental factors of malaria incidence in Kecamatan Gebang. This study was an observational analytical with case control design. The sample of this study amounted to 106 respondents with details of 53 cases and 53 controls. The univariate and bivariate were used to analyze the data. The results showed that were a relationship between habit of going out at night (p = 0,000; OR = 10,513), use of mosquito repellent (p = 0,036; OR = 2,710), existence of breeding place (p = 0,000; OR = 5,077), distance of breeding place (p = 0.011 OR = 2.963), existence of resting place (p = 0.003; OR = 4.313), and livestock cage (p = 0,000; OR = 10,014). The conclusion of this study is that there is a relationship between habit of going out at night, use of mosquito nets, existence of breeding places, distance of breeding places, existence of resting places, and existence of livestock cages related to malaria incidence in Gebang.